Feasibility study of a geothermal power plant in the Ölfus region - Nicolo Secondo Rech 1996- (2024)
The aim of the thesis is to examine the risk in building a geothermal power plant in Iceland. This is done by examining multiple elements such as finance, geophysics, geology, environmental impact assessment, permits, industry and alternative energy usage (Alkaline water electrolysis). Early exploration indicated an abundance of ground water as well as the presence of certain characteristics located below the surface. Furthermore, the financial model showed a great return on investment as well as being profitable. An alkaline water electrolysis model demonstrated profits to be even higher if the market price allows. Lastly, the permit process is discussed and evaluated. Please find the attached NDA, must be locked till 2100